Experimental Study on Cutting Force in Thermal - Assisted Machining by Induction Heating for SKD11 steel - Mac, Thi Bich; Pham, Thi Hoa; Banh, Tien Long; Nguyen, Duc Toan (Old Journal, 2018)
This paper investigated the cutting force in thermal - assisted machining (TAM) by induction heating using SKD11 material. Experiments were first performed at room temperature. Experiments were then performed at elevated temperatures to evaluate effect of heating process and compare with conventional machining method. An orthogonal array -Taguchi method and analysis of variance ANOVA method were used to design experiment, evaluate influence of control parameters on the cutting force. Results of sudy showed the cutting force reduced deeply by machining assisted by heating. Optimum values for (TAM) of SKD11 steel were obtained by cutting speed of 280 mm/min, feed rate of 230 mm/min, cutting depth of 0.5 mm and temperature of 400°C. Finally, cutting force model at elevated temperatures which was established agreed well with experimental results.